2015
DOI: 10.1182/blood.v126.23.3697.3697
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Idelalisib and ONO/GS-4059 in Lymphoma Cell Lines Sensitive and Resistant to BTK Inhibitors

Abstract: Idelalisib (Zydelig™), a first-in-class, selective, oral inhibitor of PI3Kδ, is approved for the treatment of chronic lymphocytic leukemia (CLL) in combination with rituximab and as monotherapy for patients with follicular lymphoma who have received at least 2 prior therapies. Despite remarkable clinical efficacy, complete responses are rare, highlighting the need to identify more effective therapies, including combinations of novel agents. GS-4059 (ONO-4059) is an investigational next generation BTK inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…ONO/GS-4059 was also evaluated in combination with other agents. Combination of idelalisib, a phophotidylinositol 3 kinase (PI3K) inhibitor [ 69 ], showed synergistic activity in inhibiting the growth of a subset of DLBCL and MCL cell lines, including 3 ABC-DLBCL cell lines (OCI-LY10, Ri-1, and TMD8) and 2 MCL cell lines (Rec-1 and JMV-2) [ 67 ]. Two mechanisms of resistance to BTK inhibitors were identified in the TMD8 cell line: a NF-kB inhibitor A20 mutation (TNFAIP3 Q143*), and a BTK mutation (C481F).…”
Section: Ono/gs-4059 In Preclinical Researchmentioning
confidence: 99%
“…ONO/GS-4059 was also evaluated in combination with other agents. Combination of idelalisib, a phophotidylinositol 3 kinase (PI3K) inhibitor [ 69 ], showed synergistic activity in inhibiting the growth of a subset of DLBCL and MCL cell lines, including 3 ABC-DLBCL cell lines (OCI-LY10, Ri-1, and TMD8) and 2 MCL cell lines (Rec-1 and JMV-2) [ 67 ]. Two mechanisms of resistance to BTK inhibitors were identified in the TMD8 cell line: a NF-kB inhibitor A20 mutation (TNFAIP3 Q143*), and a BTK mutation (C481F).…”
Section: Ono/gs-4059 In Preclinical Researchmentioning
confidence: 99%
“…Further investigations of ONO/GS-4059 are ongoing to ascertain its advantages in combination therapies. Combination of idelalisib and ONO/GS-4059 synergistically inhibited the growth of a subset of DLBCL and MCL cell lines [ 71 ]. This combination led to more significant growth inhibition of the A20 mutant TMD8 cells than single agent idelalisib.…”
Section: Introductionmentioning
confidence: 99%
“…Six showed a response to tirabrutinib when concentrations up to 10,000 nM were used; four of these were derived from ABC-type DLBCL (TMD8 with EC50 of 4.5 nM; OCI-LY10, U2932, and HBL1 each with an EC50 of approximately 3000 nM). The other responding cell lines were Pfeiffer, a GCB-DLBCL with an EC50 of around 3000 nM, and REC1, an MCL line with an EC50 of 33 nM [ 10 ]. The cell line most sensitive to tirabrutinib was the CD79B mutant cell line TMD8.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, tirabrutinib-resistant TMD8 which had PLCγ2 R665W was examined by combination therapy. It has been reported that tirabrutinib in combination with idelalisib, entospletinib, and the BCL2 inhibitor ABT-199 synergistically increased apoptosis in primary CLL cells, a subset of DLBCL and MCL cell lines [ 10 , 18 , 19 ]. Interestingly, the BTK Cys481S mutation activated cell-cycle reprogramming besides AKT activation [ 20 ], while the CDK4/6 inhibitor palbociclib, in combination with tirabrutinib, showed strong synergy in our resistant model, TMD8R, which does not have BTK Cys481S.…”
Section: Discussionmentioning
confidence: 99%